"Experiential Retail Environments" in the Fashion Sector. (2nd September 2022) - Servais, Elisa; Katelijn, Quartier; Jan, Vanrie
Abstract: This article examines the phenomenon of "Experiential Retail Environments" (EREs) in the fashion sector in view of being useful to retail design practice. A discovery-oriented research approach was applied to understand: (i) what an ERE is; (ii) how in-store experience is triggered; and (iii) how the experiential dimension is integrated in the retail designer's processes. Data were collected through the combination of a literature review and interviews conducted with representatives of the stakeholder groups most concerned with fashion retail design projects: retailers, retail designers, and customers. The research provided valuable clarifications. First, it helped to propose two definitions for the term ERE, one more specifically suited to a retail professional audience and the other accounting for the customer perspective. Second, it showed in-store experience to be created at two levels: through the combination of tangible aspects that generates varying customer perceptions, representing a more conceptual level for the experience. Finally, it surfaced that though there is a call for more experience integration in the fashion retail sector, currently, there is no systematic approach for this in the physical retail design process. In most cases, experiential considerations are left to the retailer and dealt with after the store concept has been designed.